Gender, politics and fiction in 1930s France - Kershaw, Angela (1998)
This study examines French political fiction of the 1930s, taking gender as its primary category of analysis. It considers texts by female novelists whose work has been largely excluded from critical attention, in order to bring their particular contribution to inter-war French literature to light. It integrates this analysis into a consideration of relevant and representative texts of the exclusively male canon of French political fiction dating from the 1930s, exploring points of contact and divergences to show how the work of the female authors relates to the wider context of French inter-war literary activity. Texts by eight writers are considered in detail, namely Madeleine Pelletier, Edith Thomas, Henriette Valet, Louise Weiss, Louis Aragon, Pierre Drieu la Rochelle, André Malraux and Paul Nizan. The analysis of the female-authored novels informs the study of their male counterparts, whose texts also offer fertile ground for an analysis in terms of gender. The corpus is approached, in broad terms, through the themes of commitment, sexuality and the body. These themes permit an investigation of the gendering of politicization as it is manifested in 1930s literature.